Flight Attendant Training Program Evaluation Based on Kirkpatrick Model - Chandra Sagul Haratua Gultom; R. Komala; Maruf Akbar (Nusantara Science and Technology Proceedings, 2020)
Training evaluation is an activity that must be carried out so that companies can believe that the training they provide can have a positive impact on improving employee performance and the company as a whole. One of them is the Flight Attendant training program at the Angkasa Training Center (ATC). The specific purpose of this research is to evaluate program implementation starting from the reaction, learning, behavior, and results which include: evaluation of program effectiveness, evaluation of program implementation, and evaluation of the impact of the program itself. Data were obtained through interview instruments, and Focus Group Discussion (FGD) through qualitative descriptive techniques. Interviews were conducted with flight attendant students, training participants' bosses, and fellow trainees, namely flight attendant students. The results of this study indicate that 1). Reaction evaluation, namely the results of reactions from students to the organizing committee and resource persons is very high. Only need to pay attention to the preparation of materials at the beginning of the training, 2). Learning evaluation, namely the ability of the competence of attitudes, knowledge, and skills of students to have a very significant assessment, 3). Behavioral evaluation, namely the implementation of the evaluation is carried out after the participants return to their respective workplaces. There was a significant increase in a behavior change from before training and after training. Behavioral changes such as attendance discipline, dress code, walking, motivating peers, good communication, and accuracy and speed in completing daily tasks, 4). Impact evaluation, namely there is an increase in the work of training alumni. Alumni can educate and guide and apply the knowledge gained from training to their peers, able to develop better training methods